The Impact of Transit Oriented Development on the Public Realm and Accessibility: A Case of Gurugram - Shrivastava, Avani (Calibrating Urban Livability in the Global South, 2024)
Transit-oriented development (TOD) is a type of urban advancement that encourages the use of residential, commercial, and recreational space within walking distance of public transit. It fosters a symbiotic relationship between dense and compact urban form to facilitate public transport access. This study aims to understand a framework established by world bank known as the “three values” (3V) of transit stations: node value, place value, and land value, including transit connectivity, centrality, quality of the built environment, safety and security, type of urban fabric, land use, and its potential, to determine how the public realm around metro stations differs from each other. TOD transforms transit stations and stops into vibrant community hubs. Placemaking further enhances their role as focal points, expanding their use for public purposes, which adds value to neighborhoods, boosts commercial districts, and connects businesses with commuters and customers. The purpose of this exercise is to evaluate the existing condition and accessibility of the metro stations along the transit network based on the TOD guiding and supporting principles. The focus is on three different metro stations (Sikanderpur, Millennium City Center, and Cyber City). This tool builds on the National TOD Guidance Document of India using six guiding principles and three supporting principles. Proximity to business districts, commercial centers, and other economic transit-oriented development (TOD) can have a significant impact on the public realm around commercial areas, creating a more vibrant, accessible, safe, and sustainable urban environment. The findings can also be used to integrate TOD guidelines and implement missing parameters in transit stations, resulting in better public space.